Effects of communication and conflict resolution skills training on marital satisfaction and mental health among Iranian couples - Askari, Mahin (2011)
This study examined the effects of communication and conflict resolution skills training on marital satisfaction and mental health among Iranian couples based on the PREPARE/ENRICH program. In this study, there were two scales used to assess marital satisfaction and mental health: the ENRICH Marital Satisfaction Scale and the General Health Questionnaire (GHQ-28). The study adopted a pre- and postcontrol group design in emphasizing the effects of communication training and conflict resolution skills on marital satisfaction and mental health. The participants in this research consisted of couples who were referred to the researcher by counseling center. The referrals were done for about two months in 2009. Their problems were marital difficulty and marital conflict, commonly categorized as marital dissatisfaction, which were identified after formal interview, testing and screening process. In order to assign the experimental and control groups, purposive sampling with random assignment was employed. One hundred and eight participants comprised of 54 married couples were divided equally between control and treatment groups and the training sessions lasted for eight weeks. In this training program,researchers focused on the dependent variables of marital satisfaction and mental health, while communication and conflict resolution skills training were the independent variables. Specifically, the t-test statistical analysis was employed to test for potential significant differences in couples’ scores of marital satisfaction and mental health between (i) the pre- and post-training scores for couples of the experimental group; and (ii) between the post-training scores of couples of the two different groups. The results indicated that training on communication and conflict resolution skills had significant positive effects on the marital satisfaction and mental health scores of the studied couples. In addition, this training program was effective in enhancing the couples’ communication skills and capabilities to resolve conflicts. On top of that, this program also affected their mental health sub-scales such as somatic symptoms, anxiety, social dysfunction, and depression. This study showed that the training investigated is relevant and useful for counseling procedures. The program presented can be regarded as an aid for family counselors in clinical and non-clinical therapy. Exclusively, the ENRICH psycho-educational program is efficient and well enough to be conducted systematically for Iranian couples. Hence,more marital counselors are recommended to be trained in applying the ENRICH program in their counseling practice.